The Bone Artifact Collection from Wadi Ti-n-Torha (Northern Tadrart Akakus, Libya): A Reappraisal Based on Technological Analysis. - Petrullo, Giacoma; Barich, Barbara E. (African Archaeological Review, 2021)
The development of technological analysis at the end of the 1900s made it possible to explore new aspects of the production of artifacts from animal materials, especially bones and teeth, by Holocene Saharan societies. Here, we reappraise a selected set of these artifacts excavated from the shelter sites of Ti-n-Torha Two Caves, Ti-n-Torha East, and Ti-n-Torha North, in the Libyan desert of the Tadrart Akakus. These sites were occupied from ca. 10,500 cal BP to 6050 cal BP, first by hunter-gatherer groups, and then by pastoralists. New methodologies have allowed us to identify trends in the selection of raw materials, animal species, and the methods and techniques used in the manufacture of the objects. Stylistic choices, in particular, are one of the most representative traits of the pre-pastoral groups that occupied this area; they are also perhaps the first evidence for significant continuity across the three sites in the mode of production of objects from teeth and bones.